Mechanical properties of silk of the Australian golden orb weavers Nephila pilipes and Nephila plumipes - Genevieve G. Kerr (Biology Open, 2018)
Silks from orb-weaving spiders are exceptionally tough, producing a model polymer for biomimetic fibre development. The mechanical properties of naturally spun silk threads from two species of Australian orb-weavers, Nephila pilipes and Nephila plumipes, were examined here in relation to overall thread diameter, the size and number of fibres within threads, and spider size. N. pilipes, the larger of the two species, had significantly tougher silk with higher strain capacity than its smaller congener, producing threads with average toughness of 150 MJ m−3, despite thread diameter, mean fibre diameter and number of fibres per thread not differing significantly between the two species. Within N. pilipes, smaller silk fibres were produced by larger spiders, yielding tougher threads. In contrast, while spider size was correlated with thread diameter in N. plumipes, there were no clear patterns relating to silk toughness, which suggests that the differences in properties between the silk of the two species arise through differing molecular structure. Our results support previous studies that found that the mechanical properties of silk differ between distantly related spider species, and extends on that work to show that the mechanical and physical properties of silk from more closely related species can also differ remarkably.